ET-1 gene expression of rat brain during ischemia and reperfusion and the protective effect of radix Salviae miltiorrhizae - Wu, W; Kuang, P; Li, Z (Journal of traditional Chinese medicine, 1997)
Endothelin-1 (ET-1) gene expression of rat brain during ischemia and reperfusion as well as the effect of Radix Salviae Miltiorrhizae (RSM) were studied with in situ hybridization. It was found that ET-1 gene expression of cerebral cortex and caudate-putamen was markedly increased both in 24 hours of ischemia and 24 hours of reperfusion groups (P < 0.01, P < 0.05). In RSM-treated rats, although the ET-1 gene expressions of ischemia and reperfusion sides were also increased as compared with contralateral cortex and caudate-putamen, they were significantly lower in RSM-treated rats than those of controls (P < 0.05, P < 0.01 respectively). The present study indicated that RSM can partly inhibit ET-1 gene expression of cerebral cortex and caudate-putamen during ischemia and reperfusion. This may be one of the protective mechanisms of RSM on cerebral ischemia and reperfusion.